A resting state fMRI study of major depressive disorder with and without anxiety. (September 2022) - Li, Gai-zhi; Liu, Peng-hong; Zhang, Ai-xia; Andari, Elissar; Zhang, Ke-Rang
Highlights: The fALFF values within the ACC and the insula were significantly lower in anxious MDD patients. The lower fALFF values was observed in women with anxious MDD, not in men. The REHO values was comparable in anxious MDD and nonanxious MDD. Abstract: Background: The neurobiology of the Major depressive disorder (MDD) with anxiety is still unclear. The present study aimed to explore the brain correlates of MDD with and without anxiety in men and women during resting-state fMRI. Methods: Two hundred and fifty-four patients with MDD (MDD with anxiety, N = 152) and MDD without anxiety, N = 102) and 228 healthy controls (HCs) participated in this study. We compared the fALFF(fractional amplitude of low-frequency fluctuations) and ReHo(regional homogeneity) of ACC(anterior cingulate cortex) and insula among these three groups. We also compared gender difference between MDD with anxiety and MDD without anxiety. Results: We found that the fALFF values within the ACC and insula were significantly lower in MDD with anxiety compared to without anxiety and HCs. However, we did not find differences in ReHo values among the three groups. In women, we found significant differences in fALFF values between MDD with and without anxiety. These differences were not observed in men. Conclusions: It is possible that MDD with anxiety show less spontaneous BOLD-fMRI signal intensity within the ACC and insula compared to MDD without anxiety, especially in women. The fALFF within the ACC and insula can be a potential biomarker for severe MDD phenotype.